Analisis Efisiensi Pada Sistem Pengeringan Bunga Rosella (Hibiscus sabdariffa L) Menggunakan Alat Pengering Tipe Lemari - Refli Safrizal; Hendri Syah; Rita Khathir (Department of Agricultural Engineering, Syiah Kuala University, 2012)
Efficiency Analysis in Drying System for Rosella (Hibiscus sabdariffa L) Using Cabinet Type DryerABSTRACT. Drying is one of the most important process in producing a good quality of rosella tea. The study was aimed to evaluate the drying efficiency of rosella tea by using a cabinet dryer. The source of energy for the dryer was from the burning of charcoal. The charcoal was prepared from the coconut shell since it was abundant biomass product. About 7.5 kg of fresh rosella flower was dried for 17 hours. The total of charcoal consumed was 17 kg. The moisture content of rosella flower was reduced from 90 to 12 %. The analysis showed that the total of energy produced from the burning of 17 kg charcoal was 309.4 MJ, whilst the total energy needed to dry the flower was 15,72 MJ. Therefore, the drying efficiency was still low about 4.58%. Further study is recommended to improve the drying efficiency for example by the use of deeper depth of dried products between 2 and 6 cm as well as by improving the system of hot air circulation.